On Fuzzy Derivation Of Fuzzy Near-ring (Journal of the College of Basic Education, 2023)
Let be a fuzzy subnear-ring of a ring R, a semifuzzy left ideal of and d is additive map on . The purpose of this paper is to prove if admits a fuzzy derivation d which is fuzzy centralizing on , then is a fuzzy commutative ideal of R.